The Impact of Technological Advances on Digital Tax Policy: A Literature Review of Online Content Creators' Taxation - Dhayan, Hana (International Journal of Applied Research and Sustainable Sciences, 2024)
This study explores the challenges and potential solutions for addressing tax evasion among digital content creators, specifically focusing on TikTokers in Indonesia. As the digital economy grows, the increasing income generated by content creators has prompted concerns about tax compliance. Using a qualitative approach with in-depth interviews and a literature review, this study identifies several factors contributing to low tax compliance, including a lack of understanding of tax obligations, unclear tax classification for content creators, and difficulties in tracking digital transactions by tax authorities. The findings suggest the need for enhanced education, clearer tax regulations specific to content creators, and improved monitoring mechanisms. Recommendations are provided for the government to increase voluntary tax compliance among content creators, contributing to more effective taxation in the digital economy.